Application of Problem-Based Learning and Scientific Approach to Self-Efficacy and Problem-Solving Ability in Reaction Rate Material - Nafisa Rahmah; Nurfina Aznam (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to determine differences in self-efficacy and problem-solving abilities of students in problem-based learning and scientific approach learning. This study uses a quasi-experimental research design with a pretest-posttest group research design. The sample used in this study consisted of two classes, namely class XI Mathematics and Natural Sciences 4 as the experimental class and class XI Mathematics and Natural Sciences 2 as the control class. A total of 70 class XI students were randomly selected as the research sample using random sampling technique. The instrument used was a test in the form of a description of the ability to solve problems and a non-test, namely a self-efficacy questionnaire. The analysis technique in this study used the Manova test and the Paired Sample T-Test. The results of this study indicate that there are significant differences in the self-efficacy and problem-solving abilities of students who take problem-based learning with students who take scientific approach learning. The contribution given by the problem-based learning model to self-efficacy and the ability to solve problems simultaneously is 71.5%, students' self-efficacy is 61.8%, and problem-solving skills is 43.3%.